2017
DOI: 10.3390/colloids1010004
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Assemblies of Gold and Silver Nanoparticles for Plasmon Enhanced Spectroscopy Using Living Biotemplates

Abstract: Abstract:The ability to control the assembly of nanoparticles on substrates used in plasmon-enhanced spectroscopy continues to drive research in the field of nanofabrication. Here we describe the use of fungi as soft biotemplates to fabricate nanostructured microtubules with gold and gold-silver nanoparticles with potential applications as sensors and biosensors. In the first step, spores of the filamentous fungus Cladosporium sphaerospermum were inoculated in a suspension of gold nanoparticles, forming stable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…In comparison to other scalable and cost-competitive noble metal colloid deposition techniques for optical sensor applications [29,30,31,32], our method is truly lithography-free and produces isolated 2D particle arrays with small and controllable gaps (20–60 nm range).…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to other scalable and cost-competitive noble metal colloid deposition techniques for optical sensor applications [29,30,31,32], our method is truly lithography-free and produces isolated 2D particle arrays with small and controllable gaps (20–60 nm range).…”
Section: Introductionmentioning
confidence: 99%
“…22 However, these successive layers cannot be simply explained in terms of chemical bonds between nanoparticles and the fungus. Therefore, some attractive interaction should occur between these nanoparticles mediated by molecules secreted by the fungus [23][24][25] . Gold or silver nanoparticles keep their colloidal stability indefinitely, but small changes in ionic strength, temperature or dielectric constant can destabilize the colloidal suspension owing to their influence on the diffuse electric double layer around each nanoparticle.…”
Section: Resultsmentioning
confidence: 99%
“…25 In our studies, we observed that the formation of subsequent multilayers could be associated to the influence of the secondary metabolites produced by living fungus due the stress caused by the presence of metal nanoparticles, since we did not observe nanoparticles deposited on the surface of dead fungus. 23,24 The interaction of these hydrophobic molecules with colloidal nanoparticles seems to be responsible by the deposition of successive layers of nanoparticles on the fungus surface.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations